Simultaneous Determination of Arsenic(III) and Arsenic(V) in Atmospheric Particulate Matter by Electrically Heated Quartz Hydride-Generation Atomic Absorption Spectrometry - Gheisari, M.M.; Talebi, S.M.; Saber-Tehrani, M. (Asian Journal of Chemistry, 2012)
A method based on hydride generation atomic absorption spectrometry (HG-AAS) using an electrically heated quartz tube was developed for simultaneous determination of As(III) and As(V) associated with total suspended particles (TSP) and PM10 particles collected from urban and rural atmosphere. The concentrations of As(III) and As(V) associated with total suspended particles and PM10 were simultaneously determined. The monthly variation in atmospheric concentrations of As(III) and As(V) was investigated and indicated that the higher concentrations were found in December, January and February, respectively. The atmospheric concentration of total arsenic was also determined in rural and urban areas and the results showed the lower atmospheric concentrations in rural area with lower traffic density. An excellent co-variation in concentrations of arsenic, PM10 and CO indicated that arsenic is mostly released into the atmosphere from anthropogenic sources and especially from combustion of fossil fuels in automobile engines.